2010
DOI: 10.5187/jast.2010.52.1.029
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Phase Feeding Methods on Growth Performance, Meat Quality, and Production Cost in Growing-Finishing Pigs

Abstract: This experiment was conducted to evaluate the influence of phase feeding methods on growth performance, carcass characteristics, pork quality, and economical efficiency in growing-finishing pigs. A total of 120 crossbred pigs ([Yorkshire × Landrace] × Duroc), average initial body weight 25.23 ± 2.66 kg, were allotted to 5 treatments by body weight and sex in a randomized complete block (RCB) design. Each treatment had 6 replicates with 4 pigs per pen. The treatments were 1) A (fed late weaner feed during whole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 1 publication
2
8
0
Order By: Relevance
“…Münchow and Bergner [29] reported that there was a highly negative correlation between the biological value of feed and BUN content. Increase of BUN concentration indicated that excessive amino acids are inefficiently metabolized and circulated in the blood before excretion [30, 31]. Although a linear response by CM supplementation level was observed at 6 week, the BUN value of all treatments were in normal range (10.0 – 30.0 mg/dL).…”
Section: Resultsmentioning
confidence: 99%
“…Münchow and Bergner [29] reported that there was a highly negative correlation between the biological value of feed and BUN content. Increase of BUN concentration indicated that excessive amino acids are inefficiently metabolized and circulated in the blood before excretion [30, 31]. Although a linear response by CM supplementation level was observed at 6 week, the BUN value of all treatments were in normal range (10.0 – 30.0 mg/dL).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Lee et al [ 26 ] represented that two or three phase feedings resulted less BUN concentration compared to that of one phase feeding. Excessive consumption of protein decreased the availability of protein [ 18 ] and increased the excretion of the nitrogen as urea form [ 15 ]. Thus, increase of BUN concentration indicated that excessive amino acids are inefficiently metabolized and circulated in the blood before excretion [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Excessive consumption of protein decreased the availability of protein [ 18 ] and increased the excretion of the nitrogen as urea form [ 15 ]. Thus, increase of BUN concentration indicated that excessive amino acids are inefficiently metabolized and circulated in the blood before excretion [ 18 ]. The result of current study was in agreement with previous researches which observed reduction of BUN concentration with supplementation of lower crude protein diet [ 6 , 7 , 13 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations